2020
DOI: 10.1093/scan/nsaa017
|View full text |Cite
|
Sign up to set email alerts
|

Self–other overlap and interpersonal neural synchronization serially mediate the effect of behavioral synchronization on prosociality

Abstract: Behavioral synchronization has been found to facilitate social bonding and prosociality but the neural mechanisms underlying such effects are not well understood. In the current study, 60 dyads were hyperscanned using functional near-infrared spectroscopy while they performed either a synchronous key-pressing task or a control task. After the task, they were asked to perform the dictator game to assess their prosocial behavior. We also measured three potential mediating variables: self–other overlap, perceived… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 72 publications
2
24
0
Order By: Relevance
“…Moreover, we only observed an association between INS and cooperative task performance and reciprocity in mother– but not father–child pairs. Future studies might be able to decipher further relevant behaviors and traits in relation to INS in father–child interactions and probe possible mediation / moderation mechanisms (see Feng et al, 2020 ). A more detailed comparison of behavioral and INS patterns in dyads consisting of mothers and fathers with their children seems to be a promising research avenue.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, we only observed an association between INS and cooperative task performance and reciprocity in mother– but not father–child pairs. Future studies might be able to decipher further relevant behaviors and traits in relation to INS in father–child interactions and probe possible mediation / moderation mechanisms (see Feng et al, 2020 ). A more detailed comparison of behavioral and INS patterns in dyads consisting of mothers and fathers with their children seems to be a promising research avenue.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, levels of cerebral synchrony varied with social distance between interacting partners (Djalovski et al, 2021;Kinreich et al, 2017), suggesting that cerebral synchrony reflects social connectedness. Indeed, available empirical evidence indicates that cerebral synchrony positively relates to explicit representation of other individuals: perceived self-other overlap and cerebral synchrony in the right dorsolateral prefrontal cortex positively mediated the prosocial effects of dyadic motoric synchrony (Feng et al, 2020). In addition, cerebral synchrony positively correlated with accuracy in inferring pain (Goldstein et al, 2018) and with convergence in self-reported emotion when the partner's emotion was accurately recognized (Anders et al, 2020).…”
Section: Interpersonal Synchronymentioning
confidence: 99%
“…When individuals are experiencing heightened feelings of closeness and connectedness, they are prompted to expand their sense of self and, consequently, their cognitive processing on the self–other boundary is blurred, leading to an enhanced sense of inclusiveness with others. In fact, existing research has shown that people’s self–other overlap perception could be influenced by the physical environment, such as the shared sensory experience (Feng et al , 2020; Quintard et al , 2021) and the peripersonal space (i.e. immediate surrounding space; Maister et al , 2015).…”
Section: Theoretical Backgroundmentioning
confidence: 99%